Doping and Surface Modification of Ti02 with Cr3+, Fe3+ and Cu2+ as Photocatalyst Materials - Nursyifa, Irsya
Photocatalyst Ti02 has been commonly used to degrade dyes but its working range is st ill limited to the range of UV light and certai n dyes. In t hi s research, doping and surface